2005
DOI: 10.1590/s1806-37132005000500009
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da vacinação de maiores de 60 anos para influenza sobre as internações e óbitos por doenças respiratórias e circulatórias em Fortaleza - CE - Brasil

Abstract: OBJETIVO: Este estudo tem por objetivo avaliar o impacto da vacina da influenza sobre internações e óbitos por doenças respiratórias e circulatórias em Fortaleza - CE. MÉTODOS: Analisaram-se os dados do Ministério da Saúde sobre óbitos (período 1995 a 2001) e internações por doenças respiratórias e circulatórias (1995 a 2003) em residentes de Fortaleza maiores de 60 anos. RESULTADOS: Ocorreram 29.867 internações por doença do aparelho respiratório. Entre 1995 e 1998, a média anual foi de 3.067,3 (desvio-padrão… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
2
0
9
Order By: Relevance
“…24 Two other studies, one conducted in the state of Ceará and the other in the state of São Paulo, showed similar results with a significant decrease in the number of deaths and in mortality rate due to respiratory and cardiac causes from 2000 to 2001, with increased mortality in later years. 25,26 A noteworthy study on mortality among the elderly in Brazil from 1980 to 2005, shows an increase in mortality related to influenza among the elderly, more pronounced in the South and Southeast regions, and among men older than 80 years, despite vaccination. 27 The reasons for these mixed results after vaccination campaigns are deficiencies in the coverage of the elderly population at risk 28 and immunosuppressive factors related to the aging immune system, reducing vaccine protection.…”
Section: Smr/100000 Inhab Femalementioning
confidence: 99%
“…24 Two other studies, one conducted in the state of Ceará and the other in the state of São Paulo, showed similar results with a significant decrease in the number of deaths and in mortality rate due to respiratory and cardiac causes from 2000 to 2001, with increased mortality in later years. 25,26 A noteworthy study on mortality among the elderly in Brazil from 1980 to 2005, shows an increase in mortality related to influenza among the elderly, more pronounced in the South and Southeast regions, and among men older than 80 years, despite vaccination. 27 The reasons for these mixed results after vaccination campaigns are deficiencies in the coverage of the elderly population at risk 28 and immunosuppressive factors related to the aging immune system, reducing vaccine protection.…”
Section: Smr/100000 Inhab Femalementioning
confidence: 99%
“…menor que para los grupos de alto riesgo en donde la vacuna ha mostrado ser costo ahorrativa (18). Respecto a los mayores de 65 años la vacunación resultó ser costo ahorrativo con resultados similares a otros estudios (19)(20)(21)(22). En el análisis de sensibilidad los resultados continúan siendo costo efectivos para menores de dos años y costos ahorrativos para mayores de 65 en cualquiera de los dos escenarios usados, pese a que hay una importante variación entre ellos, lo que sugiere que los estimados presentados aquí son robustos frente a variaciones de los estimadores epidemiológicos.…”
Section: Discussionunclassified
“…Varios estudios muestran que la vacunación de menores de dos años reduce la morbilidad y mortalidad asociada a influenza en adultos mayores (16,(19)(20)(21). La inclusión de este efecto rebaño puede incrementar dramáticamente el costo efectividad de la vacunación en niños (20).…”
Section: Discussionunclassified
“…Considerando que foram utilizadas taxas padronizadas por idade, que minimizam o efeito potencial do envelhecimento populacional nas comparações temporais das taxas de mortalidade, faz-se necessário investigar outras explicações para os incrementos observados. 26 Além disso, descreveu-se de maneira preliminar, certo achatamento das amplitudes dos picos máximos de incidência da taxa de mortalidade pelas causas selecionadas no Brasil e nas Regiões Sul e Sudeste após 1998 -ano da introdução das campanhas de vacinação contra influenza na população alvo deste estudo. O achado sugere um possível efeito protetor da vacinação de maneira semelhante à hipótese discutida por Freitas (2004), porém as elevações observadas para as taxas de mortalidade após o ano 2000, especialmente entre os idosos mais velhos, reforçam a necessidade de investigação em estudos específicos com este objetivo.…”
Section: Discussionunclassified